Pathways to Northeast: considerations on direct and indirect impacts of return migration in recent time - Ojima, Ricardo (2015)
We seek to analyze the relationship with the recent changes in migration flows in Brazil, more specifically, the increasingly importance of return migration and its indirect effects, with special emphasis on the Brazilian Northeast. Through recent demographic census data it was observed the importance of return migration flows to Northeast and from family members of these returned persons (i.e. the indirect effects). Thus, this analysis allows us to recognize migrants as a social group, noting their main characteristics. The characterization of these flows is configured as an important element in new spaces of migration in Brazil, especially for the Northeast.